Adversity Quotient dan Kecemasan Menghadapi Dunia Kerja Pada Mahasiswa Tingkat Akhir - Anita Gregah Dewantari; Christiana Hari Soetjiningsih (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
This research aims to determine the relationship between the adversity quotient and the anxiety of final year students in dealing with the world of work at various universities in Indonesia. This research was conducted using a correlational quantitative method by involving final year students from various universities in Indonesia. The samples in this research were taken by means of non probability techniques, specifically with the type of accidental sampling. The data analysis method used is the Pearson product moment correlation method. The results showed that there was a significant negative relationship between Adversity Quotient and anxiety in dealing with the world of work with r value = -0.731 and significance = 0.000 (p<0.05). Thus, it may be inferred that the higher adversity quotient level will be more likely to reduce the level of anxiety in dealing with the world of work. On the other hand, the lower level of adversity quotient will be more likely able to increase the level of anxiety in dealing with the world of work. Adversity quotient was managed to provide an effective contribution of 50.8% to anxiety in dealing with the world of work. Therefore, this research is expected to be a provision of knowledge to increase or form an adversity quotient in reducing anxiety in facing with the world of work. Penelitian ini bertujuan untuk mengetahui hubungan antara Adversity Quotient dan kecemasan menghadapi dunia kerja pada mahasiswa tingkat akhir dari berbagai perguruan tinggi di Indonesia. Partisipan dalam penelitian ini berjumlah 170 mahasiswa dari berbagai Perguruan tinggi di Indonesia dengan menggunakan teknik sampling accidental. Metode analisis data yang digunakan yaitu dengan metode korelasi Product Moment dari Pearson. Hasil penelitian menunjukkan bahwa adanya hubungan negatif yang signifikan antara Adversity Quotient dan kecemasan dalam menghadapi dunia kerja dengan nilai r = -0,731 dan signifikansi = 0,000 (p<0,05). Artinya semakin tinggi Adversity Quotient maka semakin rendah munculnya kecemasan dalam menghadapi dunia kerja, dan sebaliknya jika Adversity Quotient rendah maka kecemasan dalam menghadapi dunia kerja semakin tinggi. Dengan demikian, penelitian ini diharapkan menjadi bekal pengetahuan untuk meningkatkan atau membentuk adversity quotient dalam mengurangi kecemasan dalam menghadapi dunia kerja.